Rendimiento en el aserrado por grados de calidad de Apariencia en taxones de pinos en el NE de Argentina - Winck, Rosa Ángela; Belaber, Ector; Aquino, Diego Rolando; Bulman Hartkopf, Christian; Rotundo, Cristian Andres; Gauchat, Maria Elena; Fassola, Hugo Enrique (Facultad de Ciencias Forestales, Universidad Nacional de Misiones (UNaM) y EEA Montecarlo, INTA, 2023)
The quality of sawn wood plays a fundamental role when its main destination is for export. The objective of this work was to evaluate the yield of sawn timber classified according to the Appearance standard. Forty-two trees from seven taxa were sampled in one test. The yield of boards without knots on one or more faces/edges was higher for trees from the dominant stratum and similar between taxa. However, there was a trend of higher wood production in the Appearance quality grades for F1, F1 × PCH y PCH and taxa. This trend could be further increased by using these hybrid materials.